2021
DOI: 10.3390/genes12060878
|View full text |Cite
|
Sign up to set email alerts
|

New Bird Sexing Strategy Developed in the Order Psittaciformes Involves Multiple Markers to Avoid Sex Misidentification: Debunked Myth of the Universal DNA Marker

Abstract: Sexing of birds is indispensable for scientific, breeding and conservation programs but is difficult in many species and is particularly problematic in the case of nestlings showing no sexual dimorphism. Most useful and efficient methods of sex determination are based on unique features of the Z and W sex chromosomes detected via PCR to distinguish males (ZZ) and females (ZW). During the last twenty-five years researchers searched for the universal marker capable of sexing a maximally wide spectrum of species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
(71 reference statements)
1
19
0
1
Order By: Relevance
“…It was suggested that the three autosomal genes could be used for normalization and autosomal controls in both clades. As found by Kroczak et al, [ 76 ] not all genes amplified in all species.…”
Section: Sexingsupporting
confidence: 60%
See 3 more Smart Citations
“…It was suggested that the three autosomal genes could be used for normalization and autosomal controls in both clades. As found by Kroczak et al, [ 76 ] not all genes amplified in all species.…”
Section: Sexingsupporting
confidence: 60%
“…Kroczak et al [ 76 ] compared markers and polymorphisms that have been used routinely and commercially as “universal markers” to identify sex in birds and found that no single universal marker can be applied to sex all birds, especially parrots, successfully. These included the two widely used markers P2P8 and CHD1iA as well as four W/Z length polymorphisms ( CHD1iE , CHD1i16 , CHD1i9 and NIPBLi16 ).…”
Section: Sexingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, accurate sex typing is a serious pitfall in many scientific, breeding and conservation programs. Over 50% of the world's bird species, nestlings, and adult individuals show no sexual dimorphism (Kroczak et al 2021). And also, sex determination is the important thing on a population or sex ratio of the population before reintroduction program (Insee et al 2014).…”
Section: Introductionmentioning
confidence: 99%